Experimental and numerical investigations of the electro-mechanical response of particle filled elastomers—Part II: Continuum modeling approach - Mehnert, Markus; Faber, Jessica; Hossain, Mokarram; Chester, Shawn A.; Steinmann, Paul (European Journal of Mechanics A-Solids, 2022)
A comprehensive experimental study performed under a combination of electro-mechanical loads on a particle-filled silicone as a representative of dielectric elastomers is presented in the Part I of this work (Mehnert et al., submitted, 2021). The constitutive modeling and numerical simulation of electro-active polymers are essential fields of research in order to increase the acceptance of this group of soft smart materials in real-life applications. However, only few contributions containing constitutive modeling approaches are combined with experimental data obtained from electro-mechanically coupled loading conditions due to the complexity of corresponding experiments. In this contribution, we aim to develop an electro-mechanically coupled model, which closely replicates the response of a silicone polymer filled with a high dielectric permittivity filler of varying fractions that are characterized under a combination of electric and mechanical loads. Once the model is calibrated with the experimental data described in Part I of this contribution, it is used for a simple illustrative application example showcasing the capability of the model and the influence of the different material characteristics.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Dielectric elastomers; Electro-active polymers; Electro-mechanics; Particle filled polymers